2022
DOI: 10.3390/ani12070911
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Survey of Dirofilaria and Leishmania Species in Dogs from Central Balkan

Abstract: Dirofilariosis and leishmaniosis are severe parasitic diseases in dogs, and their causative agents can also be pathogenic to humans. In this study, we conducted a multicentric survey in the regions of Serbia and North Macedonia with the goal to establish an epidemiological scenario of dirofilariosis and leishmaniosis in the territory of Central Balkan. Using molecular analyses, a total of 535 dogs from Northern Serbia (NS), Southern Serbia (SS) and North Macedonia (NM) were screened for the presence of Dirofil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…pipiens is related to the presence of irrigated areas, a high density of human population and animals infected by D. immitis and/or D. repens and an increase in humidity. Moreover, if we take into account the wild carnivore population ( 7 , 13 , 24 , 25 , 27 , 79–82 ) and others ( 82 ), our model increases in reliability as studies of Dirofilaria spp. infected animal populations show concentrated positivity, as well as infected domestic dogs, in the north of the country.…”
Section: Discussionmentioning
confidence: 99%
“…pipiens is related to the presence of irrigated areas, a high density of human population and animals infected by D. immitis and/or D. repens and an increase in humidity. Moreover, if we take into account the wild carnivore population ( 7 , 13 , 24 , 25 , 27 , 79–82 ) and others ( 82 ), our model increases in reliability as studies of Dirofilaria spp. infected animal populations show concentrated positivity, as well as infected domestic dogs, in the north of the country.…”
Section: Discussionmentioning
confidence: 99%
“…However, epidemiological studies from Serbia have shown increased prevalence, with ranges between 12.7 and 33.3% in the north of the country, together with the presence of some microfilaremic dogs [7,[68][69][70][71]. In the Republic of Kosovo, antigens of D. immitis were detected in 14.8% of the dogs tested [72], being the first evidence of infected dogs in this country. In Bosnia and Herzegovina, there are no previous studies demonstrating the presence of D. immitis in dogs in these countries before 2011 [2].…”
Section: Endemic Areas (■) and Sporadic Cases Reported (■) )mentioning
confidence: 91%
“…In conclusion, we report a case of D. repens microfilaremia in a professional soldier frequently exposed to vector biting because of prolonged outdoor activities during military training in northern Serbia, a dirofilariasis-endemic area ( 10 ). The presence of circulating microfilariae highlighted by this and previous studies shows the parasite’s progressive adaptation to humans and suggests a potential role for humans as a definitive D. repens host.…”
mentioning
confidence: 89%